IMPLEMENTASI TINGKAT KEMATANGAN BUAH MONK DENGAN MENGGUNAKAN EKSTRAKSI GRAY-LEVEL CO-OCCURRENCE MATRIX (GLCM) DAN SUPPORT VECTOR MACHINE (SVM) - Dadang Iskandar Mulyana; Dewi Riyanti Wibowo (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Monk fruit is a fruit from China which is believed to have many benefits and properties. This fruit, which belongs to the pumpkin family, is often used as a sweetener, a good substitute for sugar, for dieters and diabetics. It has a slightly oval round shape with a green skin color. Each fruit has characteristics that are used to determine its quality. However, fresh monk fruit is rarely found in the market because it spoils quickly. Information on the maturity level of Monk fruit is needed by the agricultural industry in general. one of the obstacles is helping which is still done manually. Therefore researchers will use GLCM and SVM calculations. At the GLCM calculation stage, a matrix is ??formed with angles of 0°, 45°, 90° and 135°. The feature values ??extracted are contrast, homogeneity, energy and correlation. And SVM is one of the methods used in digital image processing to extract features. This study used 991 Monk fruit datasets. There are two classes,